2022
DOI: 10.1259/bjrcr.20210154
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral type IIpersistent proatlantal intersegmental artery: a rare variant of persistent carotid-vertebrobasilar anastomoses

Abstract: The persistent proatlantal intersegmental artery is a rare variant of persistent carotid-vertebrobasilar anastomoses, especially their bilateral presence is rarer. We report a case of bilateral typeII persistent proatlantal intersegmental artery. The absence of bilateral vertebral arteries was incidentally noted on neck ultrasound examination. Subsequent time-of-flight MR angiography confirmed this. The bilateral typeIIpersistent proatlantal intersegmental artery arose from the cervical external carotid artery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
0
2
1
Order By: Relevance
“…The incidence in this study of PPIA is approximately 0.01%. Additionally, PPIA has been reported to occur bilaterally in the literature [8,9], whereas in this study, it was observed unilaterally.…”
Section: Discussioncontrasting
confidence: 52%
“…The incidence in this study of PPIA is approximately 0.01%. Additionally, PPIA has been reported to occur bilaterally in the literature [8,9], whereas in this study, it was observed unilaterally.…”
Section: Discussioncontrasting
confidence: 52%
“…One such anomaly to be aware of is a persistent proatlantal intersegmental artery, 13 also known as a persistent first intersegmental artery, where the vertebral artery courses between the C1/2 levels, rather than on top of C1. A persistent proatlantal intersegmental artery occurs in approximately 2% of patients, 13 and all spine surgeons should be aware of this dangerous, aberrant course of the vertebral artery. Second, although navigation was not used in the current study, it may be useful to optimize localization, specifically in an unfamiliar approach that requires a steep learning curve and a high spatial awareness.…”
mentioning
confidence: 99%
“…In their reported case of endoscopic C2 root ganglionectomy, Yu et al 3 performed a cervical 3D computed tomography angiography surgery at C1-C2 and recommended it as a routine preoperative evaluation to avoid vertebral artery anomalies. One such anomaly to be aware of is a persistent proatlantal intersegmental artery, 13 also known as a persistent first intersegmental artery, where the vertebral artery courses between the C1/2 levels, rather than on top of C1. A persistent proatlantal intersegmental artery occurs in approximately 2% of patients, 13 and all spine surgeons should be aware of this dangerous, aberrant course of the vertebral artery.…”
mentioning
confidence: 99%